Attainment and Gender Equality in Higher Education: Evidence from a Large Scale Expansion - Asena Caner; Merve Demirel; Cagla Okten (Institute of Labor Economics (IZA), 2019)
We examine the dramatic expansion in the Turkish higher education system during 2006-2008, which resulted in the establishment of 41 new public universities and a 60% increase in the number of available slots. Using the variation in the exposure intensity of expansion across cohorts and regions, we estimate the causal effect of the expansion on overall attainment and the gender gap in higher education. Before the expansion, women had lower higher education rates. The expansion increased the attainment rates of both men and women but failed to reduce the gender gap. Comparing the scale of expansion across fields of study, we observe that the largest growth in available slots was in social sciences and engineering. The expansion of slots in social sciences benefited men and women evenly, but the expansion in engineering benefited men more than women, thereby raising the gender gap.
Keywords: I23; I24; I28; 330; higher education expansion; educational attainment; gender gap; Turkey